2015
DOI: 10.1038/ncomms10215
|View full text |Cite
|
Sign up to set email alerts
|

Cdk1 orders mitotic events through coordination of a chromosome-associated phosphatase switch

Abstract: RepoMan is a scaffold for signalling by mitotic phosphatases at the chromosomes. During (pro)metaphase, RepoMan-associated protein phosphatases PP1 and PP2A-B56 regulate the chromosome targeting of Aurora-B kinase and RepoMan, respectively. Here we show that this task division is critically dependent on the phosphorylation of RepoMan by protein kinase Cyclin-dependent kinase 1 (Cdk1), which reduces the binding of PP1 but facilitates the recruitment of PP2A-B56. The inactivation of Cdk1 in early anaphase revers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
85
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 66 publications
(90 citation statements)
references
References 37 publications
4
85
0
1
Order By: Relevance
“…Therefore, we sought to narrow down the residues required to interact with Cyclin B1. A region of the RepoMan protein between amino acids 403-550 had been reported to bind Cyclin B1 (Qian 2015), and when we compared this region to exon 4 of MAD1 we found a small region of similarity ( Figure 1B). This region of MAD1 is predicted to be part of helical region (using the JPred program, Cole et al, 2008), and likely to form a coiled-coil structure (McDonnell et al, 2006).…”
Section: Resultsmentioning
confidence: 86%
See 1 more Smart Citation
“…Therefore, we sought to narrow down the residues required to interact with Cyclin B1. A region of the RepoMan protein between amino acids 403-550 had been reported to bind Cyclin B1 (Qian 2015), and when we compared this region to exon 4 of MAD1 we found a small region of similarity ( Figure 1B). This region of MAD1 is predicted to be part of helical region (using the JPred program, Cole et al, 2008), and likely to form a coiled-coil structure (McDonnell et al, 2006).…”
Section: Resultsmentioning
confidence: 86%
“…The binding of Cyclin B1 to unattached kinetochores has been observed by a number of groups Bentley et al, 2007;Chen et al, 2008), and this 'guilt by association' is one piece of evidence implicating Cyclin B1-CDK1 in the mechanics of the SAC and chromosome attachment. The problem in interpreting previous studies designed to elucidate the role of Cyclin B1-CDK1 in the SAC is the many SAC-independent roles that the kinase plays: it prevents cells from separating their sister chromatids and exiting mitosis; it maintains outer kinetochore structures; it prevents the activation of Cdh1; and it represses phosphatase activity (Holt et al, 2008;Qian et al, 2015;Visintin et al, 1998;Zachariae et al, 1998). Additional caveats are introduced in studies using small molecule inhibitors, which can affect other Cyclin-CDK1 family members and related kinase families.…”
Section: Discussionmentioning
confidence: 99%
“…The most prominent interaction is that mediated by pS670 BR1 /pS591 RM , which binds H187 B56 and R188 B56 . Previous work showed that in vivo substitution of the anchoring pS residue with a D is not phosphomimicking (Qian et al, 2015). Our structures reveal why this is the case: an Asp is too short to effectively reach the R188 B56 side chain.…”
Section: Resultsmentioning
confidence: 99%
“…The invariant SLiM residues place some constraints on the type of kinase inputs that are tolerated within the motifs themselves (supp. fig.7), but phosphorylation outside of these regions can also regulate phosphatase binding (Kumar et al, 2016;Qian et al, 2015). Furthermore, PP1 uses co-operative interaction with other SLiMs, and some of these, such as the SILK motif in Knl1, are also phospho-inhibitable (Liu et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, up to 25% of the validated motifs are known to be phosphorylated in vivo, and 50% of the RVxF and 100% of the LxxIxE motifs contain phosphorylatable residues at the key positions ( fig.6c-e); which is a statistically significant enrichment (see amino acid matrices in supp.table.1). It should be noted that phosphorylation of residues outside of the core RVxF region can also inhibit PP1 binding (Kumar et al, 2016;Qian et al, 2015). Furthermore, the negatively charged surface that surrounds the RVxF pocket on PP1 ( fig.6f), could potentially mediate many other electrostatic interactions that are inhibitable by phosphorylation.…”
Section: Phospho-regulation Is a Common Feature Of Rvxf And Lxxixe Slimsmentioning
confidence: 99%